E-145 Saskatchewan experience with mechanical thrombectomy under general anaesthesia. (22nd July 2019) - Persad, A; Ahmed, S; Tymchak, Z; Whelan, R; Gardner, A; Hunter, G; Graham, B; Peeling, L; Kelly, M
Abstract : Background: While recent clinical trials have demonstrated immense efficacy of mechanical thrombectomy in the setting of acute stroke; there remains debate over the relative safety in performing this procedure under general anesthesia (GA). Recent RCT and meta-analyses have not provided a definitive answer to this question. With the reorganization of stroke systems of care, as a result of the Saskatchewan Acute Stroke Pathway, all patients presenting with LVO are assessed and endovascular thrombectomy is performed routinely under GA. We reviewed data from our pathway to add to the data regarding safety of thrombectomy under GA. Methods: Data was retrospectively reviewed on 154 consecutive LVO in 2016–2018 at the only Comprehensive stroke center in Saskatchewan. All patients undergoing MT were place under GA for the procedure. Pretreatment National Institutes of Health stroke scale (NIHSS), location of LVO and ASPECTS score were documented. Post-thrombectomy TICI scores, time to revascularization, and 90-day outcomes, both NIHSS and mRS, were recorded. Results: Of 154 LVO, 147 went on to have mechanical thrombectomy (MT). 65 were right anterior circulation, 70 were left anterior circulation and 11 were posterior circulation. Of 135 anterior circulation strokes, 69 (51.1%), 58 (42.9%) and 8 (5.7%) had good, moderate and poor collateral circulation respectively, and the average pre-MT ASPECTS was 8.2. The average pre-MT NIHSS was 13.4. The average time from groin puncture to revascularization was 48.7 min. A total of 133/147 (90.4%) achieved thrombolysis in cerebral infarction (TICI) perfusion scale grade of 2b/3 after recanalization. On follow-up, 70/147 and 90/147 had documented 90-day National Institutes of Health stroke scale (NIHSS) (average = 2.4) and 90-day modified Rankin score (mRS) (average = 2.2). Overall mortality was 29/147 (19.7%). Conclusions: In a high volume Comprehensive Stroke Center, general anesthesia is safe to always use mechanical thrombectomy. Outcomes of mechanical thrombectomy for LVO in are in keeping with published results for both conscious sedation and general anesthesia. This adds to the body of evidence supporting GA as a excellent option for sedation for mechanical thrombectomy. It is particularly useful in more complex cases and leads to high revascularization rates. Disclosures: A. Persad: None. S. Ahmed: None. Z. Tymchak: None. R. Whelan: None. A. Gardner: None. G. Hunter: None. B. Graham: None. L. Peeling: 2; C; Medtronic. M. Kelly: 2; C; Medtronic.